2007
DOI: 10.1021/la062956e
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Fibronectin Adsorption on TiO2 Surfaces

Abstract: In the present work we analyze the dynamics of fibronectin (FN) adsorption on two different stable titanium oxides, with varied surface roughness, and chemically similar to those used in clinical practice. The two types of titanium oxide surfaces used were TiO2 sputtered on Si (TiO2 sp) and TiO2 formed on commercially pure titanium after immersion in H2O2 (TiO2 cp). Surface characterization was previously carried out using different techniques (Sousa, S. R.; Moradas-Ferreira, P.; Melo, L. V.; Saramago, B.; Bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 68 publications
6
65
1
Order By: Relevance
“…Cell adhesion to several material surfaces is dependent on the prior adsorption of specific serum proteins, including fibronectin and vitronectin, 53 which support cell attachment to the surface and influence cell morphology. [54][55][56] In this study, we demonstrated that hMSC morphology was affected by the underlying surface topography, specifically in terms of cell spread and the number of filopodia.…”
Section: Discussionmentioning
confidence: 99%
“…Cell adhesion to several material surfaces is dependent on the prior adsorption of specific serum proteins, including fibronectin and vitronectin, 53 which support cell attachment to the surface and influence cell morphology. [54][55][56] In this study, we demonstrated that hMSC morphology was affected by the underlying surface topography, specifically in terms of cell spread and the number of filopodia.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest to note that the measured roughness value for the lower protein surface coverage corresponding to Ra = 1.8 ± 0.2 nm is lower than for the bare surface. This could indicate a partial filling of "valleys" with FN molecules as was observed for the adsorption of FN molecules into valleys on titanium oxide surface [32] or the "cavities" on a poly(ethylene glycol) substrate [33]. The increased deposition of fibronectin on the substrate in the middle of the deposit (as previously confirmed from the fluorescence data analysis) led to the increased roughness observed in this area which may be related to disorder in the arrangement of adsorbed protein molecules [33,34].…”
Section: Protein Deposition Characterisationmentioning
confidence: 57%
“…The deposition of fibronectin was Previous studies [30,32,33] have demonstrated that proteins may be deposited with functional integrity using various methods to maintain protein stability. In this study the assessment of protein function has been extended by studying the cellular response to electrospray deposits.…”
Section: Discussionmentioning
confidence: 99%
“…5) as well as the aspect ratio of the nanostructures. And many researches demonstrated that the protein adsorbed on the nanostructures would mediate the cell nanotopographical interactions via the mechanotransductive cascade [27,28].…”
Section: Resultsmentioning
confidence: 99%